(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The main task of modern society, the change in educational policy in general and in the field of teaching speech disciplines are discussed in this article. An analysis of pedagogical practice and the results of special studies suggest that the problem of using these technologies to develop the speech competence of future specialists of non-linguistic universities in the process of teaching the Russian language has not yet been adequately reflected in the research of scientists. It is also said that many problems in higher education, in particular, the use of pedagogical technologies in teaching the Russian language, are poorly solved in both theoretical and practical aspects